DIALEKTIKA WACANA ISLAM DAN POLITIK - Hamdan Hamdan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2017)
This article aims to retrace the relationship between Islam and politics and the accompanying discourse dialectics. This is important because Islam, at least in the past decade, has become a prominent issue in the global political arena, including in Indonesia, especially with regard to radicalism and khilafah issues. Problems arise when universal principles in Islamic teachings are to be grounded in the context of state life and cultural diversity underlying them. There are two approaches that underlie various thoughts about Islamic and political relations, namely structural approaches and cultural approaches. In the context of the relationship between Islam and the State and the penetration of Western political thought into the Islamic world, Islamic thinkers are divided into three schools of thought. First group; develop ideas of the perfection of Islamic teachings and reject the influences of Western thought. Second group; trying to separate Islam from politics. Third group; striving to take the middle of the two currents of thought above.